Feasibility and acceptability of a physical activity intervention to reduce prenatal cannabis use: results of an open pilot trial - Battle, Cynthia L.; Dreyer-Oren, Sarah E.; Vijil Morin, Andrea; Hoyt, Morgan N.; Metrik, Jane; Abrantes, Ana M (Frontiers in Psychiatry, 2026)
Cannabis is commonly used among reproductive-aged individuals, and prenatal cannabis use (PCU) has increased dramatically in recent years, despite guidance warning of possible adverse outcomes. Physical activity interventions have been shown to reduce substance use in other populations. Building on this, we examined the feasibility and acceptability of a 10-week prenatal walking intervention in a small trial with 16 pregnant individuals who were seeking to reduce PCU. Participants wore a Fitbit to track activity and attended 6 sessions designed to promote gradual increases in daily step count. Indicators of feasibility, acceptability and safety were assessed, as were changes in cannabis use, physical activity, depression and anxiety. Results suggest the intervention was feasible and acceptable; most women (88%) completed the intervention, attending on average 5.8 of 6 sessions, with strong compliance to Fitbit wear. No adverse events were reported. Findings provide preliminary evidence for intervention efficacy: 62.5 percent of participants endorsed PCU at baseline vs. 16.6% by the 36 week assessment; in addition, by endpoint, physical activity increased from an average daily stepcount of 5738 at baseline to 6562, and anxiety and depression were significantly lower. Participants reported high satisfaction with the intervention on a satisfaction survey and in an interview. Participants voiced appreciation for the accountability provided by the intervention, and support for making gradual, achievable changes in behavior. Though preliminary, findings suggest a physical activity intervention could be a valuable strategy to help reduce PCU. Further research is needed to evaluate the intervention in a more rigorous controlled trial.